Optical diagnosis of malignant colorectal polyps: is it feasible? - van der Vlugt, Manon; van Doorn, Sascha Corrie; Wang, Junfeng; Bastiaansen, Barbara AJ; Brosens, Lowewijk AA; Fockens, Paul; Dekker, Evelien (Endoscopy International Open, 2016)
Background and study aims: As colorectal cancer screening programs are being implemented worldwide, an increasing number of early (T1) cancers are being diagnosed. These cancers should be recognized during colonoscopy because they require a specific therapeutic approach. Several studies have shown that Asian experts can reliably recognize T1 cancers during colonoscopy. In daily practice, however, accurate endoscopic diagnosis of T1 cancers still seems challenging. We evaluated the performance of optical diagnosis of T1 cancers by European colonoscopy experts, general gastroenterologists and gastrointestinal fellows. Patients and methods: We collected endoscopic images of 43 colonic lesions: 19 T1 cancers (excluding intramucosal carcinoma) and 24 benign polyps ranging from 7 mm to 30 mm in size. Seven colonoscopy experts, 7 general gastroenterologists, and 14 gastrointestinal fellows assessed these images. We calculated sensitivity, specificity, negative predictive value (NPV) and positive predictive value (PPV) and their 95 % confidence intervals for optical diagnosis of T1 cancers. Results: Overall sensitivity for correct diagnosis of T1 cancers was 60 % (95 % CI;45 – 72). Sensitivity was highest for experts (67 %: 95 %CI; 48 – 81), when compared to general gastroenterologists (53 %: 95 %CI; 37 – 69) and gastrointestinal fellows (59 %: 95 %CI;45 – 72). The overall NPV was 75 % (95 %CI;60 – 86); NPV was lowest for general gastroenterologists 72 % (95 %CI;57 – 83) vs 78 % (95 %CI;63 – 89) for experts and 75 % (95 %CI;60 – 85) for gastrointestinal fellows. Conclusions: In this image-based study, both sensitivity for the optical diagnosis of a T1 cancer and NPV for excluding a T1 cancer were insufficient. Experts performed best with a sensitivity of 67 % and a NPV of 78 %, while the performance of fellows in the last year of training was comparable to that of experts. Our study indicates that training for endoscopic diagnosis for T1 cancers is urgently needed to ensure optimal clinical practice for treatment of these lesions.